Primary viral-secondary bacterial pneumonia: a novel Syrian hamster infection model for investigating modulation of host response pathways as therapeutic targets - Romano, Ashley, author; Slayden, Richard, advisor; Abdo, Zaid, committee member; Bosco-Lauth, Angela, committee member; Podell, Brendan, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2025)
Acute respiratory tract infections remain a significant public health concern. Despite numerous clinical retrospective studies on primary viral-secondary bacterial pneumonia (VBP), there are no experimental reports addressing the influence of SARS-CoV-2 on susceptibility to secondary bacterial infection, VBP studies exploring the effects of biological variables, or assessment of host-directed therapeutics (HDTs) as a treatment strategy for VBP using immunocompetent lab animal model species. As such, I designed a three-pronged research project to address these critical knowledge gaps to create a novel small animal infection model with high translational impact for studying human VBP pathogenesis and treatment options. I first established an infection model characterizing VBP in Syrian hamsters, which is an immunocompetent lab animal species that is naturally susceptible to SARS-CoV-2 and extracellular bacterial species. I found that the ideal infection scenario comprised of: male hamsters older than 39 weeks of age; intranasal SARS-CoV-2 administered on Day 0; non-surgical intratracheal Haemophilus influenzae serotype B administered on Day 2.5 post-viral infection (PVI); study endpoints of Day 7 and Day 14 PVI. I then repeated this experiment and included virus-only, bacteria-only, and bacteria followed by virus infection groups to confirm that the pathogen infection sequence impacts disease phenotype. This study demonstrated that the virus followed by bacteria infection group resulted in the greatest amount of weight loss, most severe histopathology, and positive microbial titers on Day 7 post-primary infection (PPI). Moreover, to assess which pathways were most affected on Day 7 PPI, I performed qRT-PCR relative gene expression on lung tissue homogenates that revealed significant pro- and anti-inflammatory gene dysregulation in a subset of virus followed by bacteria infected hamsters that was not detected in any other infection group. These findings informed the choice of HDTs selected to modulate host pathways implicated in host-pathogen interactions that can lead to severe disease states. I discovered that either modulating expression of host receptors utilized by SARS-CoV-2 for cell entry or modulating host cyclooxygenase-2 function may be viable treatment targets for subsets of VBP patients. Together, this work establishes a new model for assessing VBP in an underutilized laboratory animal species and highlights the utility of HDTs as a treatment option for VBP.
Keywords: secondary bacterial pneumonia; COVID-19; Syrian hamster